Mexico (Journal of Parents and Teachers, 2026)
It provides an overview of Mexico, covering its geography, economy, society and history. It also discusses key figures such as Hernán Cortés and Benito Juárez, who played a fundamental role in the formation of the Mexican state.
Keywords: Mexico, history, conquest, revolution and society.